Genetic Diversity of Diaphorina citri and Its Endosymbiont Across Diffusion Frontier and Epidemic Areas of Citrus Huanglongbing in China - Jin Yang; Ai-Jun Huang; Jun Zhou; Ping You; Xiang Li; Han Luo; Long Yi (Diversity)
Citrus huanglongbing (HLB) is one of the most severe diseases affecting the citrus industry, with Diaphorina citri (Hemiptera: Liviidae) serving as its primary natural vector. To understand the genetic diversity and population structure of D. citri in the context of HLB diffusion, we analyzed 13 populations from the HLB diffusion frontier and 25 populations from epidemic areas in China. The HLB diffusion frontier areas refer to the peripheral regions of HLB distribution in China, including the western Zhejiang, southern Jiangsu, northern Jiangxi, northern Hunan, and eastern Sichuan provinces. In contrast, the HLB epidemic areas represent regions in China where HLB is actively widespread and causing significant impacts. We utilized mitochondrial genes (COI, ND5, and Cytb) of D. citri and housekeeping genes (dnaQ, rpoC, and argH) of its endosymbiont Candidatus Carsonella ruddii (Ca. C. ruddii) for this analysis. Our findings revealed that the D. citri and Ca. C. ruddii in different regions showed low haplotype diversity and nucleotide diversity. While the genetic variation in D. citri populations primarily occurred within populations, the endosymbiont showed contrasting patterns in the HLB epidemic areas. We identified three dispersal paths: (1) migration of the Yunnan population to Sichuan, Guizhou, and Guangxi; (2) movement of the Guangdong population to Fujian, Jiangxi, and Zhejiang; and (3) dispersal of the Guangdong population to Hunan and Guangxi. Our study suggests that D. citri populations at the HLB diffusion frontier are predominantly transmitted from neighboring epidemic areas.